The nexus of stakeholder engagement and sustainability performance: A Systematic literature review and research agenda - Nursida, Nina; Oktaviani, Rona Naula; Hudayati, Ataina (Jurnal Akuntansi dan Auditing Indonesia, 2025)
This study systematically reviews the relationship between stakeholder engagement and corporate sustainability performance, with the aim of identifying prevailing trends, research gaps, and potential future directions. Employing a Systematic Literature Review (SLR) using the PRISMA protocol, relevant studies were extracted from the Scopus database under rigorous inclusion and exclusion criteria. The review reveals that stakeholder engagement exerts a positive influence on sustainability performance across social, environmental, and economic dimensions, although this relationship is moderated by regulatory contexts, governance mechanisms, and organizational communication strategies. Stakeholder Theory emerges as the dominant theoretical lens, while alternative perspectives, such as Dialogic Theory remain underexplored within the literature. Practically, this study provides insights for companies and policymakers seeking to strengthen stakeholder engagement initiatives, enhance transparency in sustainability reporting, and support regulatory frameworks that promote inclusivity. Academically, it contributes a comprehensive synthesis of existing research, outlines key trends and unresolved issues, and offers direction for future studies on stakeholder engagement in corporate sustainability.